Fecundity of tench (Tinca tinca L.) females in Lake Drwęckie - E. Pimpicka (Acta Ichthyologica et Piscatoria, 1991)
Absolute and relative fecundity was estimated for 136 tench females in Lake Drwęckie as well as the dependence between absolute fecundity and fish body weight and length, as also between ovary weight and fish age. Absolute fecundity amounted to from 18.4 to 416.1 thousand eggs, and relative fecundity from 85.7 to 543.9 thousand eggs per l000g of fish body weight. Most strict correlation was observed between absolute fecundity and ovary weight, and - successively-body weight, body length and female age. Linear relation was found between absolute fecundity and ovary and body weight, whereas power relation was noted between absolute fecundity and fish length and age.